Collecting and registering sexual health information in the context of HIV risk in the electronic medical record of general practitioners: a qualitative exploration of the preference of general practitioners in urban communities in Flanders (Belgium). Issue 4 (21st October 2015) - Vos, Jolien; Pype, Peter; Deblonde, Jessika; Van den Eynde, Sandra; Aelbrecht, Karolien; Deveugele, Myriam; Avonts, Dirk
Abstract : Background and aim: Current health-care delivery requires increasingly proactive and inter-professional work. Therefore, collecting patient information and knowledge management is of paramount importance. General practitioners (GPs) are well placed to lead these evolving models of care delivery. However, it is unclear how they are handling these changes. To gain an insight into this matter, the HIV epidemic was chosen as a test case. Methods: Data were collected and analysed from 13 semi-structured interviews with GPs, working in urban communities in Flanders. Findings: GPs use various types of patient information to estimate patients' risk of HIV. The way in which sexual health information is collected and registered, depends on the type of information under discussion. General patient information and medical history data are often automatically collected and registered. Proactively collecting sexual health information is uncommon. Moreover, the registration of the latter is not obvious, mostly owing to insufficient space in the electronic medical record (EMR). Conclusions: GPs seem willing to systematically collect and register sexual health information, in particular about HIV-risk factors. They expressed a need for guidance together with practical adjustments of the EMR to adequately capture and share this information.